Психіатрія в Україні – минуле, теперешне, майбутнє - Підкоритов, В.С. (Фізико-хімічний інститут ім. О.В.Богатського НАН України, 2008)
Показана история развития психиатрии в украине со времен Киевской Руси (Х в.) до настоящего времени. Проанализировано современное состояние психиатрической науки и практики в стране. Отмечены успехи и недостатки в работе психиатрических учреждений. Даны перспективы дальнейшего совершенствования их деятельности. It was shown the history of psychiatry’s development in Ukraine from times of Kyivska Rus (X century) until present time. It was also analysed modern state of psychiatric science and practice in out country. As well as it was admitted the progress and disadvantages in psychiatric institutions’ functioning. In addition it was outlined the prospects of their further functioning’s perfection.